Spatial and Temporal Profile of Glycine Betaine Accumulation in Plants Under Abiotic Stresses - Annunziata, Maria Grazia; Ciarmiello, Loredana Filomena; Woodrow, Pasqualina; Dell’Aversana, Emilia; Carillo, Petronia (Frontiers in Plant Science, 2019)
Several halophytes and a few crop plants, including Poaceae, synthesize and accumulate glycine betaine (GB) in response to environmental constraints. GB plays an important role in osmoregulation, in fact, it is one of the main nitrogen-containing compatible osmolytes found in Poaceae. It can interplay with molecules and structures, preserving the activity of macromolecules, maintaining the integrity of membranes against stresses and scavenging ROS. Exogenous GB applications have been proven to induce the expression of genes involved in oxidative stress responses, with a restriction of ROS accumulation and lipid peroxidation in cultured tobacco cells under drought and salinity, and even stabilizing photosynthetic structures under stress. In the plant kingdom, GB is synthesized from choline by a two-step oxidation reaction. The first oxidation is catalyzed by choline monooxygenase (CMO) and the second oxidation is catalyzed by NAD+-dependent betaine aldehyde dehydrogenase. Moreover, in plants, the cytosolic enzyme, named N-methyltransferase, catalyzes the conversion of phosphoethanolamine to phosphocholine. However, changes in CMO expression genes under abiotic stresses have been observed. GB accumulation is ontogenetically controlled since it happens in young tissues during prolonged stress, while its degradation is generally not significant in plants. This ability of plants to accumulate high levels of GB in young tissues under abiotic stress, is independent of nitrogen (N) availability and supports the view that plant N allocation is dictated primarily to supply and protect the growing tissues, even under N limitation. Indeed, the contribution of GB to osmotic adjustment and ionic and oxidative stress defense in young tissues, is much higher than that in older ones. In this review, the biosynthesis and accumulation of GB in plants, under several abiotic stresses, were analyzed focusing on all possible roles this metabolite can play, particularly in young tissues.